NILAI KESELARASAN PADA POLA TATA RUANG DESA PELANG KENIDAI KECAMATAN DEMPO TENGAH KOTA PAGARALAM SEBAGAI SUMBER PEMBELAJARAN SEJARAH - zubaidah zubaidah (KRONIK : Journal of History Education and Historiography, 2017)
The spatial of Pelang Kenidal Village was born from the philosophy and concept of the local community which has a harmony value to the life patterns of the local community. The purpose of this study was to analyze the value of the harmony in the spatial pattern of Pelang Kenidal village which will be used as techniques use several methods such as interviews, documentation, literature study, and observation. The data analysis process uses four ways, namely data collection, data reduction, data presentation, and drawing conclusions. From the results of this study it can be concluded that the value of harmony in the village spatial pattern has a value on how the life pattern and spatial structure of the Pelang Kenidal village community has a circular shape with the mosque as its center and the long hall which is a place of discussion relevant to be used as a source of learning in high schools. Because the value of harmony in this spatial pattern contains cultural values, mutual cooperation, religious, cooperation, kinship and harmony values. Keywords:  Alignment Value, Spatial Pattern, Pelang Kenidal Village, Pagaralam City